Neotypification and recognition of Polianthes geminiflora (Lex.) Rosa (Agavaceae) - Solano, Eloy; García-Mendoza, Abisaí (Instituto de Ecología, A.C., 2013)
Polianthes geminiflora (Lex.) Rose (Agavaceae) is neotypified and its detailed description is presented. This species was described by Juan José Martínez de Lexarza as Bravoa geminiflora and published in Novorum vegetabilium descriptiones in 1824. According to Lexarza, the plant was collected in the mountains of Valladolid, nowadays Morelia, Michoacán. In 1903 J. N. Rose transferred Bravoa geminiflora to P. geminiflora. Polianthes geminiflora has the widest geographical distribution and the highest morphological variation of the genus. Within P. geminiflora three infraspecific taxa have been recognized, P. geminiflora var. clivicola, P. geminiflora var. geminiflora and P. geminiflora var. pueblensis. Furthermore, we include a key to distinguish varieties and a list of herbarium specimens consulted.